Pengaruh Motivasi, Komunikasi dan Lingkungan Kerja Terhadap Semangat Kerja pada PT Global Konstruksi Prakasa Madiun - novy rachma herawati; Jefri Dwi Herdiyansyah; Mintarti Indartini (Universitas Merdeka Madiun, 2021)
Employee morale is highly dependent on the state of the work environment. The level of employee morale individually will be different depending on each employee's perception of his work. This study aims (1) Does motivation partially affect work morale at PT Global Kontruksi Prakasa Madiun. (2) Does communication partially affect work morale at PT Global Kontruksi Prakasa Madiun. (3) Does the work environment partially affect morale? work at PT Global Kontruksi Prakasa Madiun. (4) Do motivation, communication, and work environment simultaneously affect the morale at PT Global Kontruksi Prakasa Madiun. The population in this study were employees of PT Global Kontruksi Prakasa Madiun during the study period. The sample size in this study amounted to 50 people. The method used in sampling is saturated sample. The research instrument used a questionnaire. The data analysis technique used classical assumption test, multiple linear regression analysis, coefficient of determination analysis, and hypothesis testing using t test and F test. The results showed that (1) Partially, motivation had no effect on morale at PT Global Kontruksi Prakasa Madiun. (2) Partially, communication has no effect on morale at PT Global Kontruksi Prakasa Madiun. (3) Partially the work environment affects the morale of PT Global Kontruksi Prakasa Madiun. (4) Simultaneously, motivation, communication, and work environment affect work morale at PT Global Kontruksi Prakasa Madiun.